Five Canalled and Three-Rooted Primary Second Mandibular Molar - Haridoss Selvakumar; Swaminathan Kavitha; Rajendran Bharathan; Jacob Sam Varghese (Case Reports in Dentistry)
A thorough knowledge of root canal anatomy and its variation is necessary for successful completion of root canal procedures. Morphological variations such as additional root canals in human deciduous dentition are rare. A mandibular second primary molar with more than four canals is an interesting example of anatomic variations, especially when three of these canals are located in the distal root. This case shows a rare anatomic configuration and points out the importance of looking for additional canals.